Learn Adobe Dreamweaver CS5 by video core training in web communication (video sneak peek) - Mairs, Candyce (Video2brain, 2010)
"This innovative product from Adobe Press combines interactive video and a full-color printed reference to teach the fundamentals of Dreamweaver CS5 as well as the basic principles of web design. Structured around the objectives of the "Web Communication using Adobe Dreamweaver CS5" exam at the Adobe Certified Associate level, this Adobe-approved product teaches how to create well-designed rich media websites with Dreamweaver"--Resource description page.
Keywords: Dreamweaver (Computer file)